AB0120 Accelerated osteogenic differentiation of human bone-derived cells in ankylosing spondylitis. (15th June 2017) - Park, Y-S; Jo, S; Sung, I-H; Kim, T-H
Abstract : Background: Ankylosing spondylitis (AS) is characterized by excessive bone formation with syndesmophytes, leading to bony ankylosis. The contribution of osteoblasts to the pathogenesis of ankylosis is poorly understood. Objectives: The aim of this study was to determine molecular differences between disease controls (Ct) and AS bone-derived cells (BdCs) during osteogenic differentiation. Methods: We confirmed osteoblastic differentiation of Ct and AS BdCs under osteogenic medium by observing morphological changes and measuring osteoblastic differentiation markers. Osteoblast differentiation was detected by alkaline phosphatase (ALP) staining and activity, and alizarin red S and hydroxyapatite staining. Osteoblast-specific markers were analyzed by qRT-PCR, immunoblotting, and immunostaining. To examine the effects of inflammation, we added AS and healthy control serum to Ct and AS BdCs, and then analyzed osteoblast-specific markers. Results: AS BdCs showed elevated basal intercellular and extracellular ALP activity compared to Ct. When osteoblast differentiation was induced, AS BdCs exhibited higher expression of osteoblast-specific marker genes and faster mineralization than Ct BdCs, indicating that these cells differentiated more rapidly into osteoblasts. ALP activity and mineralization accelerated when serum from AS patients was added to Ct and AS BdCs. Conclusions: Our results revealed that AS BdCs showed significantly increased osteoblastic activity and differentiation capacity by regulating osteoblast-specific transcription factors and proteins compared to Ct BdCs. Active inflammation caused by adding AS serum accelerated bony ankylosis. Our study could provide useful basic data for understanding the molecular mechanism of ankyloses in AS. Disclosure of Interest: None declared